Les insectes vivants dans l’espace anthropisé. Incarnations de la dichotomie nature/culture en architecture - Delphine Lewandowski (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The systematic and unanticipated presence of insects in buildings exemplifies a paradox in the very essence of architecture: to shelter the human body against the undesirable nature that these creatures symbolize. Living insects are part of an unthought field of nature in architecture, as they are often considered undesirable, but also because of scale, space, and time issues. The dichotomies that are associated with them: “desirable/undesirable”, “controlled/uncontrolled”, or “fascination/repulsion”, illustrate the impact that naturalism has on contemporary architectural culture and its production, at a time when the integration of the living in the built environment is increasingly desired and standardized. What interactions, whether desired or uncontrolled, exist between architecture and living insects? This article proposes to question the different places that humans grant insects inhabiting the anthropized space, and to measure the impact of different forms of human/insect cohabitation on spatial production in a broad sense: using the architectural scale to examine its integration into urban spaces with territorial interventions. Three representations of insects are presented: “pest”, “useful” and “subject”, each illustrating specific architecture/nature relationships that are defined using neologisms derived from environmental ethics.